Influences of Drought and Microbial Water‐Retention Fertilizer on Leaf Area Index and Photosynthetic Characteristics of Flue‐Cured Tobacco†. (11th July 2019) - Yang, Xu; Shao, Xiaohou; Mao, Xinyu; Li, Minhui; Zhao, Tingchao; Wang, Feng; Chang, Tingting; Guang, Jianfang
Abstract: Drought has become a severe and frequently happening issue in the Guizhou province of China due to unevenly distributed rainfall and long‐term continuous cropping. Since drought and continuous cropping could be significant in causing the soil environment to deteriorate, measures which are beneficial for improving the growth of crops need are of great concern. In this study, drought conditions and a microbial water‐retention fertilizer (MWF) were applied as influencing factors for the leaf area index (LAI) and photosynthetic characteristics of flue‐cured tobacco. Under different drought conditions, the largest leaf area was obtained in normal conditions combined with 45 g basin −1 MWF (T13), which significantly increased by 32.0% when compared to normal conditions combined with 0 g basin −1 MWF (T1). An index model was further used to validate the above‐mentioned results and the correlation coefficients of LAI among different treatments were precisely simulated (0.981–0.993). The MWF had remarkable effects on tobacco's net photosynthetic rate ( P n ), stomatal conductance ( G s ), intercellular CO2 concentration ( C i ) and transpiration rate ( T r ) . Furthermore, normal conditions (550 mm irrigation) combined with MWF (45 g basin −1 ) proved to be the preferable strategy for improving water use efficiency as well as the tobacco plantation. The results might provide theoretical and practical guidance for the growth of crops in areas with water shortage. © 2019 John Wiley & Sons, Ltd. Résumé: La sécheresse est devenue un problème grave et fréquent dans la province chinoise du Guizhou en raison des précipitations inégalement réparties et de la culture continue à long terme. Étant donné que la sécheresse et les cultures en continu pourraient détériorer de manière significative l'environnement du sol, les mesures favorables à l'amélioration de la croissance des cultures suscitent de grandes inquiétudes. Dans cette étude, les conditions de sécheresse et les engrais de rétention d'eau microbiens (MWF) ont été appliqués comme facteurs d'influence de l'indice de surface foliaire (LAI) et des caractéristiques de photosynthèse du tabac jaune libre. Sous différentes conditions de sécheresse, la plus grande surface foliaire a été obtenue en conditions normales combinées avec 45 g/MW de bassin (T13), ce qui a considérablement augmenté de 32.0% par rapport à la normale combinée avec 0 g/MW de bassin (T1). Un modèle d'indice a ensuite été utilisé pour valider les résultats susmentionnés et les coefficients de corrélation de LAI entre différents traitements ont été simulés avec précaution (0.981–0.993). La MWF avait des effets remarquables sur le taux de photosynthèse nette ( P n ) du tabac, la conductance stomatique ( G s ), la concentration de CO2 intercellulaire ( C i ) et le taux de transpiration ( T r ). En outre, la stratégie normale (irrigation de 550 mm) combinée à des MWF (45 g/bassin) s'est avérée être la stratégie préférable pour améliorer l'efficience de l'eau et de la plantation de tabac. Les résultats pourraient fournir des indications théoriques et pratiques sur la croissance des cultures dans les zones de pénurie d'eau. © 2019 John Wiley & Sons, Ltd.